REINTEGRATING HUMANITY: NURSING IN THE FACE OF THE TRIPLE VULNERABILITY OF PEOPLE LIVING WITH HIV - Cervera Vallejos, Mirtha Flor (2025)
When a society allows one or more of its members to be expelled from the human network because they are HIV carriers, we all suffer moral impoverishment. Faced with this ethical fracture, it is important to reflect on how nursing deploys its most noble skills: defending the essence of the person not only with eloquent speeches, but with concrete, everyday gestures from the home, through hospital services, to every space where dignity is at risk. This mission is an imperative of justice and intellectual honesty. However, the restoration of humanity does not fall solely on professional care. It also requires collective ethical courage, with transparent management that guarantees rights, protects confidentiality, and punishes discrimination. Only in this way can the desires that stigma tried to bury be rebuilt and paths be opened for each person to be recognized in their deepest truth: their irreducible dignity.